2018
DOI: 10.1002/jcb.27438
|View full text |Cite
|
Sign up to set email alerts
|

miR‐381‐3p restrains cervical cancer progression by downregulating FGF7

Abstract: This study aimed at elucidating the molecular mechanism of miR-381-3p in cervical cancer progression, which may provide a novel therapeutic target for patients with cervical cancer. The expression of miR-381-3p was confirmed by quantitative reverse transcription polymerase chain reaction. Microarray analysis was conducted to screen out differentially expressed genes, and the target gene of microRNA (miRNA) was predicted on TargetScan. Dual-luciferase reporter assay then verified the targeting relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…14 Recent studies have suggested that miR-381-3p level was decreased in several cancers and overexpression of miR-381-3p inhibited cell proliferation and metastasis, and induced cell cycle arrest and apoptosis. [15][16][17][18][19] However, the functions and mechanisms of miR-381-3p in NPC are still unclear. In our study, miR-381-3p was observed to be down-regulated in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent studies have suggested that miR-381-3p level was decreased in several cancers and overexpression of miR-381-3p inhibited cell proliferation and metastasis, and induced cell cycle arrest and apoptosis. [15][16][17][18][19] However, the functions and mechanisms of miR-381-3p in NPC are still unclear. In our study, miR-381-3p was observed to be down-regulated in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factors (FGFs) is a heparin-binding gene family involved in various cellular and pathophysiological processes such as embryonic development, cell growth, morphogenesis, tissue repair, tumor migration and invasion (20,21,22). FGFs perform different functions by binding and activating members of the FGF receptor (FGFR) family.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, its anti-tumor role has been increasingly revealed in other malignancies such as in cervical cancer [27] and in prostate cancer [28] through the different mRNA targets. Here our study found that Second, the findings above triggered us to further explore the downstream molecules of miR-381.…”
Section: Discussionmentioning
confidence: 99%